Coronavirus COVID-19 disease, mental health and psychosocial support - Stankovska, G.; Memedi, I.; Dimitrovski, D. (Society Register, 2020)
The current coronavirus (COVID-19) pandemic is a particular and rare situation. COVID-19 has affected and is likely to affect people from many countries, in many geographical locations. We are in the midst of a worldwide pandemic, with cities and even entire countries shutting down. The coronavirus has affected nearly every aspect of our lives, from school to work, to sports, to where we eat and what we do. All these changes affected people physically, but also psychologically. It is understandable that during times like this, people may be feeling afraid, worried, anxious, and depressed due to the constantly changing alerts and media coverage regarding the spread of the virus. Hence, the main aim of our paper is to explore the linkage between the coronavirus COVID-19 disease and mental health conditions, such as stress, anxiety and depression. Everyone may experience fear of the consequences of the infection with a potentially fatal new virus, and might experience mental stress, anxiety, loneliness, depression. Based on experience from past global serious viral experiences, the development and implementation of mental health assessment, support, treatment, and services are crucial and pressing goals for the health response to the COVID-19 outbreak. Human beings have an incredible ability to adapt and survive, through altruistic and co-operative means. So for each one of us is important to look after ourselves and each other.